1994
DOI: 10.1148/radiology.192.2.8029421
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging in acute infectious cellulitis.

Abstract: The precise extent of acute cellulitis and the presence of necrotizing soft-tissue infections can be determined with MR imaging, particularly on T2-weighted images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(62 citation statements)
references
References 0 publications
1
58
1
2
Order By: Relevance
“…Compared to patients with NSTI, leukocytosis is commonly present (84%) (11,29) (29,32 (17). CT (37) or MRI (38) (50)(51)(52)(53), resulting in up to a 50% mortality rate within 48 hours after admission (54). Most…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Compared to patients with NSTI, leukocytosis is commonly present (84%) (11,29) (29,32 (17). CT (37) or MRI (38) (50)(51)(52)(53), resulting in up to a 50% mortality rate within 48 hours after admission (54). Most…”
Section: Laboratory Testsmentioning
confidence: 99%
“…It has been suggested that magnetic resonance imaging (MRI) may represent an accurate, non-invasive tool for the early diagnosis of fascial necrosis [15, 22, 23, 24]. In patients with negligible or absent skin disease and acute swelling, MRI findings (thickening of the skin and high T 2 -weighted image intensity) are limited to the skin adipose tissue and superficial fascia.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Early fascial biopsy and histopathological analysis is useful in cases where the diagnosis is unclear. Magnetic Resonanace Imaging (MRI) may also be useful as it can differentiate between necrotising fasciitis and cellulites [5].…”
Section: Introductionmentioning
confidence: 99%